The Multipurpose Application WeChat: A Review on Recent Research - Montag, Christian; Becker, Benjamin; Gan, Chunmei (Frontiers in Psychology, 2018)
With currently over one billion monthly active users, the Chinese social media and multi-purpose application WeChat (微信,Wēixìn, micro-message) has become one of the world’s most popular social media platforms. Despite its enormous number of users in Asia, WeChat is still not well-known in Western countries. Against this background, the present review aims to provide the reader with a comprehensive overview on the functionality of this application, comparison with other popular applications such as Facebook/WhatsApp and previous research. Although WeChat has become an integral part of everyday life for many users, research has only recently begun to examine the impact of this development on the societal and individual level. The present review summarizes literature on this topic with a focus on the motives to engage in using the app and potential detrimental effects of excessive use. In the context of the growing popularity and increasing usage times of the app – in particular in Asian countries – future research seems warranted to systematically examine how social media platforms such as WeChat will affect interpersonal communication behavior, well-being and mental health. Of high importance will be also the direct comparison of WeChat’s influence on the mentioned variables compared to its competitors Facebook and WhatsApp often used in Western countries.